ANALYSIS OF THE HEAVY METAL CHROMIUM (Cr) IN MULLETS (Mugil dussumieri) SPECIES IN THE WAI RUHU GALALA RIVER AMBON CITY - Wurlianty, Benjamina; Mose, Windi; Wael, Syahran (Universitas Pattimura, 2023)
The heavy metal chromium (Cr) is one of the heavy metals which is toxic and h armful if it accumulates in the body of organisms at high concentrations. Heavy metals can accumulate through the food chain, namely the higher the level of the food chain occupied by an organism, the accumulation of heavy metals in the body also increases. The aim of the research was to determine the liver contamination of mullet exposed to chromanum metal. The method used in this study was the purposive sampling method. Sediment and mullet at the Basic Kimia FKIP Laboratory while to measure the content of heavy metal Cr in sediment and mullet at the Karpan Health Laboratory, Ambon 11 Desember 2022 - 18 Januari 2023 using the AAS (Atomic Absorption Spectrophotometer). The Cr content in the sediment and mullet obtained at the estuary of the Wai Ruhu Galala river, Ambon City is still below a predetermined threshold. The research results obtained from the content of heavy metal cr in the sediment which is equal to 9,2888 Ppb while in mullet it is equal to 5,8185 Ppb. The presence of heavy metal cr is caused by contaminants which may originate from community activities around this location in the form of housedold waste coated with cr metal discharged directly into the water body such as household appliaces coated with cr metal and cans paint.